2017
DOI: 10.1097/mpg.0000000000001482
|View full text |Cite
|
Sign up to set email alerts
|

NASPGHAN Clinical Practice Guideline for the Diagnosis and Treatment of Nonalcoholic Fatty Liver Disease in Children

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a highly prevalent chronic liver disease that occurs in the setting of insulin resistance and increased adiposity. It has rapidly evolved into the most common liver disease seen in the pediatric population and is a management challenge for general pediatric practitioners, subspecialists and for health systems. In this guideline, the expert committee on NAFLD (ECON) reviewed and summarized the available literature, formulating recommendations to guide screening and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
846
2
35

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 742 publications
(1,004 citation statements)
references
References 167 publications
19
846
2
35
Order By: Relevance
“…There are no uniformly accepted pharmacological therapies recommended for paediatric NAFLD other than weight loss and exercise. Some of the situations for when a biopsy may be indicated in NAFLD are listed in box 3 but discuss cases with tertiary hepatology services for any child with persisting increased ultrasound echogenicity, elevated transaminases or splenomegaly 15
Indications for biopsy in paediatric non-alcoholic fatty liver disease (adapted from refs 15 and 16)

Diagnostic uncertainty.

Non-obese.

Splenomegaly.

Under 8 years of age.

Evidence of hepatocellular dysfunction or portal hypertension.

Persistently raised aminotransferases despite 6 months of lifestyle modification.

…”
Section: When Should I Worry?mentioning
confidence: 99%
See 1 more Smart Citation
“…There are no uniformly accepted pharmacological therapies recommended for paediatric NAFLD other than weight loss and exercise. Some of the situations for when a biopsy may be indicated in NAFLD are listed in box 3 but discuss cases with tertiary hepatology services for any child with persisting increased ultrasound echogenicity, elevated transaminases or splenomegaly 15
Indications for biopsy in paediatric non-alcoholic fatty liver disease (adapted from refs 15 and 16)

Diagnostic uncertainty.

Non-obese.

Splenomegaly.

Under 8 years of age.

Evidence of hepatocellular dysfunction or portal hypertension.

Persistently raised aminotransferases despite 6 months of lifestyle modification.

…”
Section: When Should I Worry?mentioning
confidence: 99%
“…There are no uniformly accepted pharmacological therapies recommended for paediatric NAFLD other than weight loss and exercise. Some of the situations for when a biopsy may be indicated in NAFLD are listed in box 3 but discuss cases with tertiary hepatology services for any child with persisting increased ultrasound echogenicity, elevated transaminases or splenomegaly 15…”
Section: When Should I Worry?mentioning
confidence: 99%
“…Hepatic fat quantification MRI is a useful tool for monitoring treatment efficacy in pediatric NASH (4).…”
Section: Nafldmentioning
confidence: 99%
“…The more benign form of simple steatosis and mild inflammation Or The summarizing term for the entire spectrum of the condition NASH "Pediatric type": macrovesicular hepatocellular steatosis with portal inflammation, with or without portal fibrosis, in the absence of ballooning degeneration and perisinusoidal fibrosis; "Adult type": steatosis with ballooning degeneration and lobular inflammation, with or without perisinusoidal fibrosis, and without portal inflammation have suggested that obesity, dyslipidemia, and insulin resistance are association factors (3)(4)(5). Although it can occur in normal-weight children, the prevalence of NAFLD in this group has been increasing in obese children (6).…”
Section: Nafldmentioning
confidence: 99%
“…Согласно данным российских эпидемиологических исследований DIREG 1 (2007) и DIREG 2 (2015), за 7 лет она Гастроэнтерология № 7 (151) / 2018 | | ГЕПАТОЛОГИЯ выросла на 10% [2]. Следует обратить особое внимание на то, что распространенность НАЖБП у детей достигла 10%, у подростков -17%, а у детей с ожирением, количество которых с каждым годом увеличивается, она равна 40-70% [3]; эти показатели послужили причиной для разработки педиатрических рекомендаций по диагностике и лечению НАЖБП у детей [4]. В Российской Федерации распростра-ненность НАЖБП среди молодых людей (от 18 до 29 лет) на 2015 год составила 19,25% [2,5].…”
unclassified